2017
DOI: 10.1142/s1088424617500638
|View full text |Cite
|
Sign up to set email alerts
|

Photoconductive behavior of binary porphyrin crystalline assemblies

Abstract: The mechanism of photoconductivity in a crystalline photoconductor synthesized from 1:1 ratio of meso-tetra(4-pyridyl)porphyrin (TPyP) and meso-tetra(4-sulfonatophenyl)porphyrin (TSPP) ionic tectons was examined. The rod-like crystals of TPyP:TSPP insulate in the dark but become photoconducting on illumination and a portion of the photoinduced current persists after the laser light is turned off. This persistent photoconductivity (PPC) is investigated as a function of laser illumination wavelength, laser power… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(44 citation statements)
references
References 55 publications
1
42
1
Order By: Relevance
“…We note that heating the BP solids up to 130 °C did not modify their elemental charges or composition, based on X-ray photoelectron spectroscopy, (XPS) measurements [18,20,28,29,36]. Thermogravimetric analysis (TGA) combined with XPS showed that the crystals experienced reversible loss of water from within their crystalline channels at temperatures below 110 °C and became amorphous with annealing above 125 °C [29,30]. Representative morphologies of BP crystals obtained from optical and SEM imaging are depicted in Fig.…”
Section: Composition and Morphologymentioning
confidence: 94%
See 4 more Smart Citations
“…We note that heating the BP solids up to 130 °C did not modify their elemental charges or composition, based on X-ray photoelectron spectroscopy, (XPS) measurements [18,20,28,29,36]. Thermogravimetric analysis (TGA) combined with XPS showed that the crystals experienced reversible loss of water from within their crystalline channels at temperatures below 110 °C and became amorphous with annealing above 125 °C [29,30]. Representative morphologies of BP crystals obtained from optical and SEM imaging are depicted in Fig.…”
Section: Composition and Morphologymentioning
confidence: 94%
“…SEM images of TPyP:TSPP ( Fig. 2d) crystals synthesized in a pH 3 solution show that the crystals have rectangular cross sections and squared off ends; the larger structures are hollow [30]. Eskelsen [35].…”
Section: Composition and Morphologymentioning
confidence: 99%
See 3 more Smart Citations